2012
DOI: 10.5539/ies.v5n1p86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooperative Learning on Students at An Giang University in Vietnam

Abstract: This study investigates the effects of jigsaw cooperative learning on the achievement and knowledge retention of 80 final-year Vietnamese mathematics students, as well as reporting their attitudes toward this form of learning. These tertiary students were divided into two matched groups of 40 to be taught by the same lecturer. In the experimental group, jigsaw learning was employed, while in the control group, lecture-based teaching was used over the six weeks of instruction. The results showed that students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 43 publications
9
64
0
9
Order By: Relevance
“…Furthermore, it has been shown that this methodology facilitates the social, emotional and psychological development of students, with regard to social support, quality relationships of students, attitude to learning and learning skills (Gillies 2003(Gillies , 2008Johnson & Johnson 1990;Pinho-Lopes, Macedo, & Bonito 2011;Smith et al 2005;Tran & Lewis 2012); specifically, Bertucci et al (2010), as well as Chen and Wang (2013) note that students' self-esteem improves in cooperative work because they are involved in cooperative efforts. Also, Johnson and Johnson, R. T. (2009) and Slavin (2011) argue that the positive relationships promoted among students by cooperative learning increase motivation, persistence and degree of commitment to the achievement of group goals, as well as productivity, satisfaction and the sense of personal responsibility for their achievements.…”
Section: Conceptualization Of the Human Person And The Suitability Ofmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, it has been shown that this methodology facilitates the social, emotional and psychological development of students, with regard to social support, quality relationships of students, attitude to learning and learning skills (Gillies 2003(Gillies , 2008Johnson & Johnson 1990;Pinho-Lopes, Macedo, & Bonito 2011;Smith et al 2005;Tran & Lewis 2012); specifically, Bertucci et al (2010), as well as Chen and Wang (2013) note that students' self-esteem improves in cooperative work because they are involved in cooperative efforts. Also, Johnson and Johnson, R. T. (2009) and Slavin (2011) argue that the positive relationships promoted among students by cooperative learning increase motivation, persistence and degree of commitment to the achievement of group goals, as well as productivity, satisfaction and the sense of personal responsibility for their achievements.…”
Section: Conceptualization Of the Human Person And The Suitability Ofmentioning
confidence: 99%
“…The development of these attitudes through cooperative learning will strengthen student's self-esteem (Bertucci et al 2010;Johnson and Johnson 1999;Johnson et al 1999b;Slavin 1991Slavin , 2011Tran and Lewis 2012), and this will enable them to manage stress and adversity, and to remain committed to attaining the primary goal they have chosen for their life (Johnson and& Johnson, 1999). The educator must respect the option chosen by the student, but his function, as guide, can be very valuable to show him how to give the most of himself.…”
Section: Commitmentmentioning
confidence: 99%
See 3 more Smart Citations